2021
DOI: 10.1021/acschemneuro.0c00822
|View full text |Cite
|
Sign up to set email alerts
|

Long Noncoding RNAs MALAT1 and ANRIL Gene Variants and the Risk of Cerebral Ischemic Stroke: An Association Study

Abstract: Cerebral ischemic stroke (CIS) is one of the primary causes of death worldwide and a major cause of long-term disability. Long noncoding RNAs (lncRNAs) have emerged as crucial mediators in the pathology of CIS; however, their potential importance is yet to be discovered. Herein, we examined the association of four single-nucleotide polymorphisms (SNPs) with the risk of CIS, their correlation with the lncRNAs, MALAT1 and ANRIL, expression, and the potential of serum MALAT1 and ANRIL as biomarkers for CIS. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
2
11
0
Order By: Relevance
“…The opposite results were obtained by Nevine Fathy et al, according to their study MALAT1 rs619586 AA and rs3200401 CT, TT was associated with an increased risk of cerebral ischemic stroke [18]. The results of our study confirm the conclusions of other scientists on the important role of polymorphisms in the gene of long non-coding RNA MALAT1.…”
Section: Genotypesupporting
confidence: 68%
“…The opposite results were obtained by Nevine Fathy et al, according to their study MALAT1 rs619586 AA and rs3200401 CT, TT was associated with an increased risk of cerebral ischemic stroke [18]. The results of our study confirm the conclusions of other scientists on the important role of polymorphisms in the gene of long non-coding RNA MALAT1.…”
Section: Genotypesupporting
confidence: 68%
“…Different experimental and clinical research has shown the anti-inflammatory and anti-apoptotic roles of Malat1 in the brain [11][12][13]. The downregulation of lncRNA Malat1 in IS patients has been reported in previous studies [12,14]. Ren et al demonstrated that Malat1 expression was inversely associated with the National Institutes of Health Stroke Scale (NIHSS) score and the expression of pro-inflammatory factors (including TNF-α, CRP, IL-6, IL-22, and IL-8) on the first day after stroke [12].…”
Section: Introductionmentioning
confidence: 67%
“…Ren et al demonstrated that Malat1 expression was inversely associated with the National Institutes of Health Stroke Scale (NIHSS) score and the expression of pro-inflammatory factors (including TNF-α, CRP, IL-6, IL-22, and IL-8) on the first day after stroke [12]. Fathy et al in 2021 also reported the downregulation of Malat1 in IS patients with a negative association with stroke severity [14] The soluble glycoproteins that are produced by microglia, astrocytes, endothelial cells, and neurons in response to damaged brain tissue are cytokines. Cytokines clearly play a key role in the pathophysiology of stroke, and a high ratio of pro-inflammatory to anti-inflammatory cytokines is associated with larger infarct volume and poorer functional outcomes in IS patients [15].…”
Section: Introductionmentioning
confidence: 99%
“…One study reported a tendency that serum MALAT1 expression levels of the TT genotype and CT + TT genotype were higher than that of the CC genotype in CRC patients [36]. A similar trend was found in serum MALAT1 expression levels between rs3200401 C>T and cerebral ischemic stroke [37]. Li et al found that MALAT1 mRNA was overexpressed in CRC tissues according to the Oncomine expression profiling database [38].…”
Section: Discussionmentioning
confidence: 85%